Antisideslip and Antirollover Safety Speed Controller Design for Vehicle on Curved Road. (24th February 2014) - Lie, Guo; Yi-bing, Zhao; Lin-hui, Li; Ping-shu, Ge; Xiao-hui, Huang
Abstract : When the drivers cannot be aware of the existing of forthcoming curved roads and fail to regulate their safety speeds accordingly, sideslip or rollover may occur with high probability. The antisideslip and antirollover control of vehicle on curved road in automatic highway systems is studied. The safety speed warning system is set before entering the curved road firstly. The speed adhesion control is adopted to shorten the braking distance while decelerating and to guarantee the safety speed. The velocity controller when decelerating on the straight path and the posture controller when driving on curved road are designed, respectively, utilizing integral backstepping technology. Simulation results demonstrate that this control system is characterized by quick and precise tracking and global stability. Consequently, it is able to avoid the dangerous operating conditions, such as sideslip and rollover, and guarantee the safety and directional stability when driving on curved road.